Simulation and Assessment of Chemical Processes in a Multiphase Environment - Barnes, Ian; Kharytonov, Mykola M. (NATO Science for Peace and Security Series C: Environmental Security, 2008)
The book reviews the current state of knowledge on the chemical and physical processes occurring in the environmental media (i) the atmosphere, (ii) the aqueous phase and (iii) soil and identifies the strengths and weaknesses of the chemical mechanisms (both explicit and condensed) currently available to simulate the multimedia environmental chemistry of volatile organic compounds (VOCs) and particulate matter in these media. Contributions examine how well this knowledge has been incorporated into different types of CT models and appraise the current status and significant issues in the development and usage of the models. Model simulations of some real world chemical perturbations to the Earth system are presented which appraise the performance of the models in relation to "real world" observations. Serious caveats in our understanding of chemical processes and their simulation in the various compartments of the Earth system are highlighted and areas are identified that need urgent improvement, in particular with respect to environmental security.